MADRASAH EDUCATION IN A SHIFTING EDUCATIONAL LANDSCAPE: NAVIGATING ADAPTATION, CONFRONTING CHALLENGES, ANDEXPLORING PROSPECTS FOR SUSTAINABLE DEVELOPMENT - Zain Fuadi Muhammad Roziqi Fath; Muqarramah Sulaiman Kurdi; Fenni Kurniawati Ardah; Abdul Wahab Syakhrani; Ansori (International Journal of Teaching and Learning, 2023)
In our comprehensive study, "Madrasah Education in a Shifting Educational Landscape: Navigating Adaptation, Confronting Challenges, and Exploring Prospects for Sustainable Development," we delved into the intricate world of Madrasah education in Indonesia. This research, conducted entirely in the past tense, aimed to understand the complex relationship between socio-political dynamics and curriculum challenges within these institutions. With their historical significance in Indonesia's education system, Madrasahs provide both religious and secular knowledge. However, their sustainability in a rapidly changing world hinged on addressing critical issues, particularly the balance between religious and secular content and the impact of socio-political factors. Our research objectives encompassed a thorough analysis of curriculum challenges, examining socio- political influences, and identifying strategies for sustainable development. We employed various research methods, including surveys, interviews, and document analysis, with strict adherence to ethical considerations. Our study's results, presented entirely in the past tense, unveiled the intricate challenges faced by Madrasahs, including curriculum content, pedagogical methods, and resource limitations, significantly affecting student learning outcomes and the alignment of Madrasah curricula with national educational goals. Socio-political dynamics were found to play a central role in shaping Madrasah education, influencing autonomy, cohesion, and cultural preservation. Moreover, our study identified key strategies, including curriculum reform, teacher training, and community engagement, offering a roadmap for the sustainable development of Madrasah education in Indonesia. Our insights can guide policymakers, educators, and communities to ensure Madrasah education's continued relevance and inclusivity in a dynamic educational landscape.